The Polar Contradiction Between “Power” And “Justice” - Harald Wiese (Homo Oeconomicus, 2022)
One might surmise that distributions (of payoffs) that result from (i) "power" or (ii) "justice" are not systematically related to each other. However, I claim the existence of a polar contradiction between these two types of distributions. The framework for my assertion is similar to the one of (Wiese et al. (eds), Rationality in Social Science: Foundations, Norms, and Prosocial Behavior, Springer, 11 ), where interpersonal comparability of utility (ICU) is defended. ICU is important in the contexts of both bargaining (the power perspective) and welfare (the justice point of view). The bargaining-framework is evoked by the Shapley value from Cooperative Game Theory and in a sociological paper by Emerson. The particular welfare perspective taken in this paper is due to Harsanyi. The current paper (but not the former one) argues for a polar contradiction in the following sense: ICU parameters in utility functions that make one bargaining agent obtain a large share of a "pie" are exactly those that attribute a small share to the very same individual from a welfare perspective.
Keywords: C71; C78; D63; 330; Emerson; Harsanyi; Balancedness; Shapley value; Interpersonal comparability of utility